Trickle infection with Heligmosomoides polygyrus results in decreased worm burdens but increased intestinal inflammation and scarring - Ariyaratne, Anupama; Kim, Sang Yong; Pollo, Stephen M. J.; Perera, Shashini; Liu, Hongrui; Nguyen, William N. T.; Coria, Aralia Leon; Luzzi, Mayara de Cassia; Bowron, Joel; Szabo, Edina K.; Patel, Kamala D.; Wasmuth, James D.; et al. (Frontiers in Immunology, 2022)
Intestinal roundworms cause chronic debilitating disease in animals, including humans. Traditional experimental models of these types of infection use a large single-dose infection. However, in natural settings, hosts are exposed to parasites on a regular basis and when mice are exposed to frequent, smaller doses of Heligmosomoides polygyrus, the parasites are cleared more quickly. Whether this more effective host response has any negative consequences for the host is not known. Using a trickle model of infection, we found that worm clearance was associated with known resistance-related host responses: increased granuloma and tuft cell numbers, increased levels of granuloma IgG and decreased intestinal transit time, and higher serum IgE levels. However, we found that the improved worm clearance was also associated with an inflammatory phenotype in and around the granuloma, increased smooth muscle hypertrophy/hyperplasia, and elevated levels of Adamts genes. To our knowledge, we are the first to identify the involvement of this protein family of matrix metalloproteinases (MMPs) in host responses to helminth infections. Our results highlight the delicate balance between parasite clearance and host tissue damage, which both contribute to host pathology. When continually exposed to parasitic worms, improved clearance comes at a cost.